Flame retardant poly(lactic acid) biocomposites reinforced by recycled wool fibers – Thermal and mechanical properties - B. Tawiah; B. Yu; S. Ullah; R. Wei; R. K. K. Yuen; J. H. Xin; B. Fei (eXPRESS Polymer Letters)
The inherently poor flame retardancy and comparatively low tensile strength of poly(lactic acid) (PLA) have limited its wide adoption as alternative ‘green’ engineering plastic in many fields. This manuscript reports the synthesis of a new phosphorus flame retardant – phenylphosphonic 3(2-aminobenzothiazole) (P-TAB) and its combination with recycled short wool fibers (WF) for improving the flame retardancy and the mechanical properties of PLA. Fourier transform infrared (FTIR), 1H, and 13C nuclear magnetic resonance (NMR) spectra proved that P-TAB was effectively synthesized. Considerable reductions in heat release rate, total heat released, CO and CO2 produced were attained with 3 wt% P-TAB and various WF loadings. The fire performance index (FPI), and fire growth index (FGI) improved by 38.2 and 48.1% respectively. The composite achieved a V-0 rating at 20 wt% WF loading and an LOI value of 28.5%. TG-IR results showed substantial reductions in evolved gaseous products. The tensile strength and Young’s modulus improved significantly with the increasing content of WF in the composite.